2021
DOI: 10.21203/rs.3.rs-266932/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social buffering in horses (Equus caballus): Influence of context, companion familiarity and companion habituation

Abstract: Social buffering occurs when the presence of one animal attenuates another’s stress response during a stressful event and/or helps the subject to recover more quickly after a stressful event. Inconsistent previous results might reflect previously unrecognised contextual influences, such as the nature of the stimulus presented or social factors. We addressed these issues in a two-part study of horses paired with familiar (16 subjects) or unfamiliar (16 subjects) companions. Each subject performed 4 tests in a c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The term social buffering has been coined to refer to this phenomenon Hennesy et al, 2009;Hostinar et al, 2014), which has been theoretically developed for over four decades (Cohen & McKay, 1984;Cohen & Wills, 1985;Dean & Lin, 1977). This effect has been observed in a wide variety of species, including humans (e.g., Ditzen et al, 2007;Kirschbaum, Klauer, Filipp & Hellhammer, 1995), squirrel monkeys (e.g., Hennessy, 1984), rats (e.g., Stanton et al, 1987) guinea pigs (e.g., Hennessy et al, 2006), horses (e.g., Ricci-Bonot, 2021), and fish (e.g., Culbert et al, 2019) under different situations such as mild everyday stressors (Albers et al, 2008), maternal separation (Coe et al, 1978) and public speech (Kirschbaum et al, 1993). Neurophysiological correlates of the effect have also been investigated (Einsenberger et al, 2007;Taylor et al, 2008).…”
Section: The Social Buffering Effectmentioning
confidence: 99%
“…The term social buffering has been coined to refer to this phenomenon Hennesy et al, 2009;Hostinar et al, 2014), which has been theoretically developed for over four decades (Cohen & McKay, 1984;Cohen & Wills, 1985;Dean & Lin, 1977). This effect has been observed in a wide variety of species, including humans (e.g., Ditzen et al, 2007;Kirschbaum, Klauer, Filipp & Hellhammer, 1995), squirrel monkeys (e.g., Hennessy, 1984), rats (e.g., Stanton et al, 1987) guinea pigs (e.g., Hennessy et al, 2006), horses (e.g., Ricci-Bonot, 2021), and fish (e.g., Culbert et al, 2019) under different situations such as mild everyday stressors (Albers et al, 2008), maternal separation (Coe et al, 1978) and public speech (Kirschbaum et al, 1993). Neurophysiological correlates of the effect have also been investigated (Einsenberger et al, 2007;Taylor et al, 2008).…”
Section: The Social Buffering Effectmentioning
confidence: 99%
“…As a herd and prey animal, a horse observing a conspecific being slaughtered could cause distress, but research in other social species, such as pigs and sheep, found this not to be the case, especially in comparison to the impact of social isolation [3][4][5]. In some contexts, the presence of one animal has been found to mitigate a conspecific's stress response during a stressful event, a concept referred to as social buffering [6,7]. Social buffering has been found to be predominantly influenced by the nature of the stressful stimulus presented, rather than by familiarity with the conspecific [7].…”
Section: Introductionmentioning
confidence: 99%
“…In some contexts, the presence of one animal has been found to mitigate a conspecific's stress response during a stressful event, a concept referred to as social buffering [6,7]. Social buffering has been found to be predominantly influenced by the nature of the stressful stimulus presented, rather than by familiarity with the conspecific [7].…”
Section: Introductionmentioning
confidence: 99%